2017
DOI: 10.15406/apar.2017.07.00260
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses to Extended Photosynthetically Active Radiation (EPAR)

Abstract: Current and future life sciences demand more data for experiments, modeling and computing. After introducing Photosynthetically Active Radiation (PAR), the quality of light was sacrificed for the quantity. PAR has an intrinsic drawback that stems from reporting light sources by a number of the irradiated quanta. In pieces of research on photosynthesis, PAR generally and appropriately is used, whereas PAR has been inappropriately used in pieces of research not dealing with photosynthesis directly as a parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Indeed, PAR induced phytochemical changes in two Brassica species, which were different according to the genotypes tested (Fallovo et al, 2009, 2011). Coincidentally, Ghasemzadeh et al (2010) as well as Pazuki et al (2017) reported similar results. Taken together, our findings are in full agreement with those previously reported.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, PAR induced phytochemical changes in two Brassica species, which were different according to the genotypes tested (Fallovo et al, 2009, 2011). Coincidentally, Ghasemzadeh et al (2010) as well as Pazuki et al (2017) reported similar results. Taken together, our findings are in full agreement with those previously reported.…”
Section: Discussionsupporting
confidence: 57%
“…Due to the concurrent action of external and internal factors, the transpiration of the green watermelon plants follows an unimodal curve that exhibits a minimum in the morning correlated with a minimal opening of the stomata and diminishing the air dehydration power, a maximum after lunch correlated with the photoactivity increase of the degree of opening of the stomata as a result of the increase of the light intensity, the temperature and the dehydration power of the air and a minimum towards the evening correlated with the decrease of the light intensity and temperature. The photosynthetically active radiation represents the part of the electromagnetic spectrum that induces photosynthesis and includes radiations with a wavelength ranging between 400 and 700 nm (Pazuki et al, 2017). They play a role in inducing photosynthesis, as well as transpiration by determining photoactive stomatic opening movements and by increasing the temperature of the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the fraction of light absorption can also inform the design of artificial lighting systems for indoor agriculture [9], such as vertical farms [10], which can lead to more sustainable and efficient methods of food production [11]. Moreover, knowledge of the fraction of light absorption can be applied in fields such as solar energy [12,13] and photovoltaics to improve energy conversion efficiency [14][15][16][17][18][19]. Understanding light absorption in plants can contribute to our understanding of global carbon cycling and its impact on climate change.…”
Section: Introductionmentioning
confidence: 99%